Evaluación del reciclado de poliestireno expandido mediante la disolución con solventes para aplicación como base de pintura a nivel laboratorio (2024)
In the present degree work, the results obtained from the tests are analyzed and discussed to evaluate the recycling process of expanded polystyrene, obtaining 20 kg of waste accumulation for dissolution in organic solvents, with the purpose of using this resulting product based on Of paint. The experiments were designed at the laboratory level in order to dissolve expanded polystyrene (EPS) using different organic solvents, specifically, 96% ethanol, 99.5% acetone and 90% thinner.